IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLE NON EXAMPLE UNTUK MENINGKATKAN PEMAHAMAN DAN KETERAMPILAN KOOPERATIF SISWA KELAS VII SMP PADA MATERI HIMPUNAN - Ariesta Kartika Sari; Muchamad Arif; Sudarsono Sudarsono; Holifah Holifah (Widyagogik, 2019)
This study aims to (1) improve the understanding of 7th-grade students on set material, (2) describe the cooperative skills of students after following the cooperative learning model type Example Non Example. This research is collaborative classroom action research. Participants in this classroom action research are 16 class 7th SMPN 2 Socah Bangkalan Madura. The stages of classroom action research in this study refer to Bachman's Spiral model (in Mertler, 2014: 19). The stages in this classroom action research consist of Plan, Action, Observation, and Reflection. The learning model applied in this study is the cooperative learning model type Example Non Example. The focus of the material in this study is the set material of Mathematics subjects. The implementation of this classroom action research consists of two cycles. The application of cooperative learning model type Example Non Example gives results that: (1) the average student understanding in the first cycle reaches 68.8%. While the understanding of students in the second cycle reached 82.5%. Students' cooperative skills in this study consist of skills: (a) appreciating contributions, (b) being in groups, (c) listening, and (d) asking. After following the implementation of the Example Non-Example cooperative learning model, the cooperative skills of students in the first cycle reached 73% (good). Whereas in the second cycle, students' cooperative skills reached 91% (very good)